The Effect of Family Support through ROMPA MATREH on the Improvement of Lower Extremity Muscle Strength in Post Stroke Patients - Dwiretnaningtyas, Rina; Suwito, Joko; Luthfiyah, Sari; Najib, Mohammad (Universitas Negeri Gorontalo, 2025)
Stroke is a sudden attack on brain tissue that causes cell death and is the second most common killer on a global scale, right after cardiovascular disease. Hemiparesis (weakness) and hemiplegia (paralysis) are motor impairments that can result from a stroke. Families must ROMPA MATREH for this reason. Those who have had a stroke can regain strength via the use of massage treatment and range-of-motion exercises. The goal of this research at Puskesmas Pucang Sewu is to find out how much of an impact family support through ROMPA MATREH has on helping stroke survivors regain strength in their lower extremities. The research strategy used in this study is a one-group pre-post test. Included in the population are all stroke patients within the working area of Puskesmas Pucang Sewu from January to August 2024, totaling 135 individuals, averaging 17 patients per month. The sample for this study includes 16 post-stroke respondents from Puskesmas Pucang Sewu, selected using purposive sampling. Data collection utilized the SOP Manual Muscle Testing to assess lower extremity muscle strength. Data analysis was performed using the Wilcoxon test. The study results indicate that the lower extremity muscle strength before ROMPA MATREH by families was predominantly in categories 2 and 3. After ROMPA MATREH by families, most participants' lower extremity muscle strength improved to category 3. Conclusion: There is an effect of ROMPA MATREH by families on the improvement of lower extremity muscle strength in post-stroke patients within the working area of Puskesmas Pucang Sewu.